Epstein–Barr Virus, the Immune System, and Associated Diseases - Chen, Mei-Ru (Frontiers in Microbiology, 2011)
Host immune system is designed (or evolved) to fight against different pathogens. Many viruses infect the immune cells for the propagation of new progenies, thus the infection may modulate the host immune homeostasis. It has been more than 45 years since the discovery of Epstein–Barr virus (EBV) from a Burkitt’s lymphoma derived cell line. The ability of EBV to transform primary B cells in vitro leads to the suggestion for its oncogenic potential. However, except the clear understanding of the role of EBV in post-transplantation lymphoproliferative disease, it remains ambiguous why such a ubiquitous virus causes malignant diseases only in a very small subset of individuals. Possible explanation is that EBV may cooperate with other environmental and host genetic factors and lead to the development of EBV associated neoplastic diseases. In addition to infecting B cells, recent studies revealed that EBV may impact host immune system more broadly than previously thought, for example the development of regulatory NKT subsets. Instead of an intensive review, this article aims to provide a linkage to recent advances on the interplay between EBV and host immune system and to inspire further studies on EBV related diseases.